Gender in public administration: looking back and moving forward - Carey, Gemma; Dickinson, Helen (2015)
In an online virtual issue, we explore the history of gender and feminism since AJPA. It is clear that two major silences exist in public administration concerning gender. The first is the place of women and gender equity within public service workforces. The second silence is the role that feminist theories could play in tackling contemporary public management challenges. We argue that there are particular contributions that feminist theories could make in relation to topics such as collaboration, boundary-spanning and skill requirements for future public sector workers. In this editorial we therefore look backwards and forwards, examining how female public sector workers are defined within state bureaucracy, and what feminism can bring to the functioning of this bureaucracy in the future. - Reproduced.
Keywords: Leadership; Public administration; Women